INDIKATOR MAKROEKONOMI DAN RETURN SAHAM SYARIAH DI INDONESIA - Utami Baroroh (Signifikan: Jurnal Ilmu Ekonomi, 2013)
The objectives of this study are to examine empirical test the long term equilibrium and simulteneous relationship between macroeconomics variables to stock return in Indonesia and to observe stock return response because shock/innovation of inflation, SBI discount rate and exchange rate Rupiah to US dollar. The data sample used in this study are monthly time series data from 2003.1 – 2010.6. Those data are SBI discount rate, inflation (CPI), exchange rate Rupiah to US dollar, money supply and stock return (IHSG). A method of analysis in this study are Granger Causality Test and Cointegration test. The empirical results shows that SBI discount rate, inflation (CPI), and exchange rate Rupiah to US dollar have causality relationship to stock return.. The cointegration test indicates that among research variables there is long term equilibrium and simultaneous relationshipDOI: 10.15408/sjie.v2i2.2421